Gender, Usia, Status Sosial, Pengalaman Kerja terhadap Persepsi Etis Mahasiswa dengan Love of Money sebagai Mediasi - Eva Wany (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
This research was conducted with the aim of analyzing the effect of gender, age, socioeconomic status and work experience variables on the love of money and ethical perceptions of accounting students. As well as to find out whether the love of money factor is the cause of ethical perceptions. Sampling in this study used a data collection method, namely purposive sampling. This study used a sample of undergraduate students at the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya, Surabaya. The number of samples used is 100 respondents. Data analysis testing in this study used SPSS Version 20. The results of this study indicated that gender had a significant effect on students' ethical perceptions, while age, socioeconomic status and work experience had no significant effect on love of money. The variables of gender, age, socioeconomic status, and work experience have a significant influence on students' ethical perceptions. In addition, in the mediating effect of the variables gender, age, socioeconomic status, and work experience have a significant influence on students' ethical perceptions through the love of money.